2017
DOI: 10.1177/1758998317729713
|View full text |Cite
|
Sign up to set email alerts
|

Optimal early active mobilisation protocol after extensor tendon repairs in zones V and VI: A systematic review of literature

Abstract: IntroductionEarly mobilisation protocols after repair of extensor tendons in zone V and VI provide better outcomes than immobilisation protocols. This systematic review investigated different early active mobilisation protocols used after extensor tendon repair in zone V and VI. The purpose was to determine whether any one early active mobilisation protocol provides superior results.MethodsAn extensive literature search was conducted to identify articles investigating the outcomes of early active mobilisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Conventionally, the protocol of ETI treatment included static splinting and immobilization for period of 6 weeks with standard rehabilitation. 7 However, after repairing extensor tendon, immobilization time span plausibly promotes the development of strong fibrous tissues at site of repair, which lessens the risk of breakage. The prospective pitfall is of forming adhesions near to repair site that leads to restricted flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, the protocol of ETI treatment included static splinting and immobilization for period of 6 weeks with standard rehabilitation. 7 However, after repairing extensor tendon, immobilization time span plausibly promotes the development of strong fibrous tissues at site of repair, which lessens the risk of breakage. The prospective pitfall is of forming adhesions near to repair site that leads to restricted flexion.…”
Section: Discussionmentioning
confidence: 99%
“…6 Early active mobilization (EAM) requires to be in a restrained way to enhance the advantages of mobilization while ignoring the harms of unlimited motion. 7 Various studies have been conducted that have shown better results for early active mobilization but there are some limitations of these studies such as some studies were conducted retrospectively, some studies enrolled clubbed cases, criteria for assessment, proportions of patients came back for follow-up and tendon numbers are not uniform. Various prospective studies do not have a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Early mobilization protocols have been proposed to apply controlled stress to a repair, limit adhesions, and provide better outcomes than immobilization. 5 6 7 8…”
Section: Zones 5–6 Extensor Tendon Reconstruction and Therapymentioning
confidence: 99%
“…Post-operative hand therapy is critical to successful restoration of extrinsic hand function while protecting tendon transfers. Numerous published protocols exist to direct hand therapists in the care of flexor (Starr et al, 2013) and extensor tendon repairs (Collocott et al, 2018) alongside dedicated hand transplant rehabilitation protocols (Bueno et al, 2014). With 120 or so hand transplants documented by the International Registry on Hand and composite tissue transplantation (Petruzzo et al, 2010), rehabilitation programs have been described across the globe, including India (Iyer et al, 2017), United States (Bueno et al, 2014), Australia, Poland and the United Kingdom (United Kingdom).…”
Section: Rehabilitation and System Componentsmentioning
confidence: 99%